Originally Posted by

**el123** Differentiate these.

$\displaystyle y = \frac{1}{\sqrt{1-5x^2}}$

$\displaystyle =(1-5x^2)^\frac{-1}{2}$

$\displaystyle =-\frac{1}{2} (1-5x^2)^\frac{-3}{2} (-10x)$

$\displaystyle =\frac{5x}{\sqrt{(x^2-5)}^3}$

Next

$\displaystyle y = x^5e^(1-3x)$

$\displaystyle =5x^4e^(1-3x)+(-3)(x^5)$

$\displaystyle =e^(1-3x)(5-3x)$

Just so you know , in that second equation , the e is supposed to be to the power of 1-3x. But latex wont let me show it for some reason. So please keep that in mind.

Can you please check those for me?? :)